Pengaruh Servant Leadership Terhadap Organizational Citizenship Behavior (OCB) - Ade Wili Putri Utami; Maya Setiawardani (Jurnal Riset Bisnis dan Investasi, 2016)
CV Yrama Widya is publishers and printing company of subject and public schools. The company has 116 permanent employees. There is a problem at CV Yrama Widya is the lack of organizational citizenship behavior of employees which one contributing factor is the lack of leadership roles serving on the company. Based on these problems, this study aims to determine the servant leadership and organizational citizenship behavior, as well as the magnitude of the effect of servant leadership on organizational citizenship behavior at CV Yrama Widya. The method used is quantitative research methods. Data analysis methods used are descriptive statistical analysis, the classical assumption test, simple correlation analysis, simple linear regression analysis, and hypothesis testing. The results showed that servant leadership is in the category both in terms of love, empowerment, vision, humility, and trust. Then the employee organizational citizenship behavior was in the category both in terms of the behavior of altruism, conscientiousness, Sportsmanship, courtesy, and civic virtue. In conclusion, there is the influence of servant leadership on organizational citizenship behavior of employees at CV Yrama Widya amounted to 59.1%.